The War on Terror and the Caribbean - Quashie, Emanuel (Perspectives on terrorism, 2023)
The Caribbean is profoundly under-represented in the prevailing scholarly literature on terrorism and counter-terrorism. Therefore, this research note provides a brief overview of the history of terrorism within the Caribbean context, presents a summary of the existing literature, and then examines the War on Terror’s impact in the region. Drawing from a qualitative research study, the analysis concludes that the War on Terror has impacted the region in several ways. For example, countries in the region have implemented new anti-terrorism legislation; made amendments to their immigration systems; implemented counter-terrorism police units; and established a Joint Regional Communication Centre and an Advanced Passenger Information System. Overall, this research note intends to support and encourage more academic discourse regarding the War on Terror and its impact on the Caribbean region.